2009
DOI: 10.1295/polymj.pj2009045
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Poly(tetramethyl-2,7-silpyrenylenesiloxane) and Its Thermal and Optical Properties

Abstract: KEY WORDS: Pyrene / Poly(tetramethylsilarylenesiloxane) / Heat-Resistant Polymer / Photoluminescence / Pyrene has been well-known to exhibit the good fluorescence property 1 and the unique emission based on its excited dimer in the fluorescence spectrum of the solution at a relatively high concentration (ca. 10 À3 mol/L) and/or of the solid state. Thus, various pyrene derivatives have been used for the emission moiety as an emitting fluorescence probe for biological analyst, electronics and photonics materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…On the other hand, poly(tetramethylsilarylenesiloxane)s where the aromatic moieties are introduced into the main chain of PDMS have been reported to exhibit the excellent thermostability as well as PDMS and the T g depending on the arylene moieties introduced. Thus, we have reported the synthesis of poly(tetramethylsilarylenesiloxane) derivatives having various aromatic moieties as arylene moieties [2][3][4][5][6]. It has been also reported that these derivatives show bathochromic and hyperchromic effects in the absorption spectra [5,6] by the silyl groups introduced onto aromatic moieties owing to the r*-p* interaction between silyl and aromatic moieties [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, poly(tetramethylsilarylenesiloxane)s where the aromatic moieties are introduced into the main chain of PDMS have been reported to exhibit the excellent thermostability as well as PDMS and the T g depending on the arylene moieties introduced. Thus, we have reported the synthesis of poly(tetramethylsilarylenesiloxane) derivatives having various aromatic moieties as arylene moieties [2][3][4][5][6]. It has been also reported that these derivatives show bathochromic and hyperchromic effects in the absorption spectra [5,6] by the silyl groups introduced onto aromatic moieties owing to the r*-p* interaction between silyl and aromatic moieties [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…Thus, we have reported the synthesis of poly(tetramethylsilarylenesiloxane) derivatives having various aromatic moieties as arylene moieties [2][3][4][5][6]. It has been also reported that these derivatives show bathochromic and hyperchromic effects in the absorption spectra [5,6] by the silyl groups introduced onto aromatic moieties owing to the r*-p* interaction between silyl and aromatic moieties [7][8][9][10][11][12]. On the other hand, pyrene is one of interesting compounds because it shows excimer emission in the fluorescence spectra at the high concentration and/or in the solid state [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The hyperchromic effects result from the enhancement of the transition moment based on the increase in the dipole moments of the HOMO and LUMO states owing to the s-p conjugation in the HOMO and the s*-p* conjugation in the LUMO. [12][13][14][15][16][17] On the other hand, the 0-0 electronic transition was observed at around 316 nm in the case of silyl-substituted diphenylfluorene derivatives (5, M1 and P1), as shown in Figure 5a, whereas it was observed at around 324 nm in the case of silyl-substituted diphenyldibenzosilole derivatives (6, M2, and P2), as shown in Figure 5b. This bathochromic shift would be due to the stabilization of the LUMO state through s*-p* conjugation induced by the replacement of the C-9 carbon in fluorene by silicon.…”
Section: Optical Propertiesmentioning
confidence: 94%
“…[12][13][14][15][16][17] The bathochromic effect has been known to be induced by lowering the energy gap between the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) states because of destabilization of the HOMO state through s-p conjugation and stabilization of the LUMO state through s*-p* conjugation. The hyperchromic effects result from the enhancement of the transition moment based on the increase in the dipole moments of the HOMO and LUMO states owing to the s-p conjugation in the HOMO and the s*-p* conjugation in the LUMO.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation